SCN10A gene polymorphism is associated with pain sensitivity and postoperative analgesic effects in patients undergoing gynecological laparoscopy - Yang Gao; Jing Li; Lin Gan; Meng Cai; Xiaofeng Lei; Jin Yu (European Journal of Medical Research)
Abstract Background Postoperative pain intensity is influenced by various factors, including genetic variations. The SCN10A gene encodes the Nav1.8 sodium channel protein, which is crucial for pain signal transmission in peripheral sensory neurons. Objectives This study aims to investigate the relationship between genetic mutations in the SCN10A gene (rs6795970) and postoperative analgesic effects following gynecological laparoscopic surgery. Methods Two hundred female patients undergoing gynecological laparoscopic surgery under general anesthesia were included. pain sensitivity was evaluated using the catastrophizing scale and pain sensitivity questionnaire (PSQ). Patients received patient-controlled intravenous analgesia with sufentanil and dexmedetomidine for 48 h post-surgery. Postoperative pain indicators, such as visual analog scale (VAS) scores, Ramsay scores, and side effects were recorded. SCN10A rs6795970 mutations were identified using MassARRAY SNP typing technology, and patients were categoried into homozygous mutant (AA), wild type (GG), and heterozygous mutation (GA) groups for analysis. Results Patients in the AA group had higher scores on the pain Catastrophizing Scale, PSQ-total, PSQ-minor, and PSQ-moderate compared to GA and GG groups (P < 0.05). VAS scores at 4, 6, and 12 h post-operation were higher in the AA group than the GG group (P < 0.05). Ramsay scores were lower in AA patients at 2 and 4 h post-operation compared to GA and GG groups (P < 0.05). The AA group exhibited more self-control analgesic pump compressions within the first 24 h post-surgery, quicker depletion of analgesics in the pump, and lower patient satisfaction with pain relief compared to GA and GG groups (P < 0.05). Conclusions Female patients with homozygous SCN10A mutations may experience higher preoperative pain scores and increased sensitivity to postoperative pain following gynecological laparoscopic surgery with intravenous patient-controlled analgesia. Trial registration: www.chictr.org.cn , registration number: ChiCTR2200062425.